Photography and death : framing death throughout history - Harris, Racheal (Bingley, U.K. : Emerald Publishing Limited, 2020)
Examining a spectrum of post-mortem images, this volume considers what death photography communicates about attitudes related to dying, mourning and the afterlife. Focusing on American examples, topics are discussed alongside contemporary representations of death, as seen in celebrity death images and forensic photography.
4.1. OWNERSHIP OF THE BODY AND THE LYNCHING IMAGE -- 4.2. Lynching and Race -- 4.3. Lynching and Segregation -- 4.4. Lynching Images -- 4.5. History and Contemporary Guilt -- 4.6. Historical Evidence and the Death Narrative -- 4.7. The Audience Within -- 4.8. The Audience Without -- 4.9. Conclusion -- Chapter 5-Ownership: Celebrity Death -- 5.1. Ownership of the Celebrity Body -- 5.2. Body Removal -- 5.3. Scene of the Crime -- 5.4. Suicide and Autopsy Photographs -- 5.5. Kurt Cobain -- 5.6. Tupac -- 5.7. THE IMAGE AS KEEPSAKE -- 5.8. Celebrity Grave Sites -- 5.9. Conclusion
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Postmortem photography -- Psychological aspects; Death -- Psychological aspects; Photography, Subjects & Themes -- General; Special kinds of photography